2014
DOI: 10.1016/j.ijrobp.2014.05.2187
|View full text |Cite
|
Sign up to set email alerts
|

18F-FMISO PET/CT Visualization of Tumor Hypoxia in Patients With Chordoma of the Mobile and Sacrococcygeal Spine

Abstract: SummaryLocal recurrence (LR) rates in chordoma patients following surgery ± radiation therapy (RT) or definitive RT are high. Tumor hypoxia is associated with radioresistance and LR. In this prospective study, [ 18 F]-FMISO-PET/CT detected hypoxic tumor sub-volumes in 60% of patients with chordoma of the mobile and sacrococcygeal spine, the majority of which were sufficiently large to allow an RT boost. Further study of hypoxia-directed, dose-escalated RT, particularly in patients at high risk for LR, is warra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A single parameter such as an ( 18 F)fluoromisonidazole-PET mapping is probably insufficient to ascertain hypoxic resistance and to escalate the dose if one considers that tumours reoxygenate during fractionated radiotherapy [31], to the point that the same imaging arguments can be used to suggest therapeutic de-escalation when reoxygenation occurs [32]. A second obstacle to targeting hypoxia with radiotherapy is that there may be spatial variations in hypoxic subvolumes [33,34]. Therefore, a critical step could be to define a reliable and reproducible diagnosis of tumour radioresistance to be repeated over the course of radiotherapy if needed.…”
Section: High Lineal Energy Transfer Radiotherapymentioning
confidence: 99%
“…A single parameter such as an ( 18 F)fluoromisonidazole-PET mapping is probably insufficient to ascertain hypoxic resistance and to escalate the dose if one considers that tumours reoxygenate during fractionated radiotherapy [31], to the point that the same imaging arguments can be used to suggest therapeutic de-escalation when reoxygenation occurs [32]. A second obstacle to targeting hypoxia with radiotherapy is that there may be spatial variations in hypoxic subvolumes [33,34]. Therefore, a critical step could be to define a reliable and reproducible diagnosis of tumour radioresistance to be repeated over the course of radiotherapy if needed.…”
Section: High Lineal Energy Transfer Radiotherapymentioning
confidence: 99%
“…Some immunohistochemical markers, like increased expression of p53, CDK4, and high Ki-67 proliferation index have prognostic value (63)(64)(65)(66), but cannot explain the difference in outcome alone. Also, expression levels of brachyury, transforming growth factor alpha (TGF-a) and fibroblast growth factor-2 (FGF-2) are correlated with recurrence (67,68). However, the mechanisms behind these markers are still unknown.…”
Section: Diagnosis and Pathologymentioning
confidence: 99%
“…The feasibility of FMISO-PET-CT guided radiotherapy with hypoxia-directed intensity modulated radiotherapy has been demonstrated in multiple tumours (63,65,66), including head and neck cancer (67). Cheney et al (68) showed that hypoxic areas could be identified with FMISO-PET-CT in 12 out of 20 chordoma of the mobile or sacrococcygeal spine. The benefits and risks of hypoxia-guided boost volumes in radiotherapy of chordoma still has to be investigated in the future.…”
Section: Role Of Nuclear Medicinementioning
confidence: 99%